2010
DOI: 10.1080/00103624.2011.528489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Agricultural Wastes on Some Soil Quality Indexes in Clay and Loamy Sand Fields

Abstract: Effects of manure (M), hazelnut husks (HH), tea waste (TEW), and tobacco wastes (TOW) on some soil quality indexes were monitored for more than 2 years in a clay field and a loamy sand field. While soil organic carbon (OC) contents were around 2% after 30 months in clay, they were generally less than 2% after 7 months in loamy sand. Organic wastes generally increased aggregate stability (AS) and field capacity and decreased bulk density (BD) of the soils. Soil pH decreased with TEW and increased with M treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 27 publications
6
49
0
7
Order By: Relevance
“…Gülser (2006) reported that increases in organic C content significantly reduced bulk density and increased total porosity and the proportion of larger aggregates, and that there was a significant positive correlation between OC and AS. Lower BD indicates increased pore space in the soil due to the aggregation of soil particles by OM amendments (Candemir and Gülser 2010). The decomposition products of OM facilitate soil aggregation (Six et al 2004).…”
Section: Discussion Effects Of Organic Waste Application On Soil Om Amentioning
confidence: 99%
See 1 more Smart Citation
“…Gülser (2006) reported that increases in organic C content significantly reduced bulk density and increased total porosity and the proportion of larger aggregates, and that there was a significant positive correlation between OC and AS. Lower BD indicates increased pore space in the soil due to the aggregation of soil particles by OM amendments (Candemir and Gülser 2010). The decomposition products of OM facilitate soil aggregation (Six et al 2004).…”
Section: Discussion Effects Of Organic Waste Application On Soil Om Amentioning
confidence: 99%
“…Many studies have reported that the addition of organic wastes to soils reduces bulk density and increases total pore space (Anikwe 2000;Marinari et al 2000;Candemir and Gülser 2010). The increase in water-holding capacity or FC due to increased soil OM can be attributed to greater macroaggregation and increased porosity (Franzluebbers 2002;Shaver et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery in aggregate stability of such physically degraded soils is important, as those studied were expected to follow the incorporation of any cementing agent, such as SMC (Curtin and Mullen, 2007). Soil organic matter has been suggested to be the most important factor in the determination of soil aggregate stability because of the significant positive relationships between these two parameters (Aksakal et al, 2015;Candemir and Gülser, 2010;Cerdà, 1998). Thus, the application of organic materials has been proposed to improve the physical properties of degraded soils (Turgut and Kose, 2016).…”
Section: Aggregate Stability (As)mentioning
confidence: 99%
“…Karıştırılarak uygulanan zeytin atığı ise toprak ve drene olan suda ölçülen pH'rı sırasıyla % 0.4-3 azaltırken, EC'ri ise % 3-25 ve % 34-73 oranında arttırmıştır. Elde edilen bu sonuçlar, yapılan bazı çalışmaların sonuçlarıyla da benzerlik göstermektedir (Kavvadias et al, 2010;Candemir and Gülser, 2011;Nektarios et al, 2011;.…”
Section: Araştirma Bulgulari Ve Tartişmaunclassified
“…Yapılan bir diğer çalışmada, araziye uygulanan zeytinyağı fabrikası atıklarının toprakta EC'yi arttırırken, pH'ı ise marjinal etkilediği bulunmuştur (Kavvadias et al, 2010). Candemir and Gülser, (2011) killi ve tınlı kumlu arazilerde hazırladıkları parsellere uyguladıkları gübre, fındıkkabuğu, çay ve tütün atıklarının toprak fiziksel özelliklerini iyileştirmeleri yanında pH ve EC'yi arttır-dıklarını bulmuşlardır. Nektarios et al, (2011) zeytin atıklarının (%12.5 ve 50) pH ve hacim ağırlığı % 19.4-32.6 oranında azaltırken, su tutma kapasitesini % 13.3-57 oranında arttırdığını bulmuşlardır.…”
unclassified